1991
DOI: 10.1017/s0890037x00027421
|View full text |Cite
|
Sign up to set email alerts
|

Germination and Root Growth of Two Noxious Weeds as Affected by Water and Salt Stresses

Abstract: Hoary cress germination decreased with lower osmotic potential. Knapweed germination was greatest at 0.0 and −0.5 MPa of osmotic potential. Salinity increases up to an electrical conductivity (EC) of 12 dS m-1 had no effect on germination of either species. Hoary cress and knapweed root growth were reduced by decreases in osmotic potential. Hoary cress root growth was not affected by increasing salinity up to an EC of 12 dS m-1. Knapweed root growth was reduced by the initial increase in salinity (4 dS m-1), b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…The published evidence and our observations, however, oppose the germination behaviour of most plants in tropical and temperate habitats, and crops and annual plants in arid environments. For these the optimum water potential for germination coincides with the soil field water capacity and seed hydration, germination rate and germinability all decrease as water potential drops (Williams & Shaykewich, 1971;Mott, 1972;Romo & Haferkamp, 1987;Cluff & Roundy, 1988;Meidan, 1989;Evans & Etherington, 1990;Choinski & Tuohy, 1991;Khatri et al, 1991;Kiemnec & Larson, 1991;Qi & Redmann, 1993;Facelli & Ladd, 1996;Swaegel et al, 1997;Al-Karaki, 1998;Rowse et al, 1999).…”
Section: Discussionmentioning
confidence: 96%
“…The published evidence and our observations, however, oppose the germination behaviour of most plants in tropical and temperate habitats, and crops and annual plants in arid environments. For these the optimum water potential for germination coincides with the soil field water capacity and seed hydration, germination rate and germinability all decrease as water potential drops (Williams & Shaykewich, 1971;Mott, 1972;Romo & Haferkamp, 1987;Cluff & Roundy, 1988;Meidan, 1989;Evans & Etherington, 1990;Choinski & Tuohy, 1991;Khatri et al, 1991;Kiemnec & Larson, 1991;Qi & Redmann, 1993;Facelli & Ladd, 1996;Swaegel et al, 1997;Al-Karaki, 1998;Rowse et al, 1999).…”
Section: Discussionmentioning
confidence: 96%
“…A subsequent study showed rapid deterioration of L. chalepense seeds: 91% were not viable after 2 mo in water and all totally disintegrated after 19 mo, while seeds in dry storage declined gradually from 66 to 70% over the first year to 17% at the end of a 5-yr period (Bruns and Rasmussen 1957). Kiemnec and Larson (1991) found that germination and root growth of L. draba decreased with incremental decreases in osmotic potential, a potential of (1.5 MPa completely inhibiting germination, whereas increasing salt concentrations had no effect on germination or root growth. In a 3Áyr study of weed species in vineyards in Crimea, Ukraine, high seed productivity of L. draba was associated with increased seed quality, such as absolute seed weight and germinability (Kozhevnikova and Mahayeva 1980).…”
Section: Reproductionmentioning
confidence: 98%
“…Hoary cress germination is limited by dry environmental conditions (Kiemnec and Larson 1991). The xeric nature of the sagebrush ecosystem restricts seed germination, emergence, and survival to microsites where moist conditions are present.…”
Section: Discussionmentioning
confidence: 99%
“…Osmotic potential can also be a factor, especially in arid areas where salt influences are more common. Kiemnec and Larson (1991) reported hoary cress germination rates of 82, 55, 11 and 0% at osmotic potentials of 0, -0.5, -1.0, and -1.5 MPa. The process of soil freezing and thawing may have also benefited germination through vertical redistribution of soil moisture upward toward the freezing layer (Heidmann and Thorud 1976).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation